Fission yeast Sec3 and Exo70 are transported on actin cables and localize the exocyst complex to cell poles. - Felipe O Bendezú; Vincent Vincenzetti; Sophie G Martin (PLoS ONE)
The exocyst complex is essential for many exocytic events, by tethering vesicles at the plasma membrane for fusion. In fission yeast, polarized exocytosis for growth relies on the combined action of the exocyst at cell poles and myosin-driven transport along actin cables. We report here the identification of fission yeast Schizosaccharomyces pombe Sec3 protein, which we identified through sequence homology of its PH-like domain. Like other exocyst subunits, sec3 is required for secretion and cell division. Cells deleted for sec3 are only conditionally lethal and can proliferate when osmotically stabilized. Sec3 is redundant with Exo70 for viability and for the localization of other exocyst subunits, suggesting these components act as exocyst tethers at the plasma membrane. Consistently, Sec3 localizes to zones of growth independently of other exocyst subunits but depends on PIP(2) and functional Cdc42. FRAP analysis shows that Sec3, like all other exocyst subunits, localizes to cell poles largely independently of the actin cytoskeleton. However, we show that Sec3, Exo70 and Sec5 are transported by the myosin V Myo52 along actin cables. These data suggest that the exocyst holocomplex, including Sec3 and Exo70, is present on exocytic vesicles, which can reach cell poles by either myosin-driven transport or random walk.